2020
DOI: 10.1002/jgm.3150
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer to skeletal muscle using hydrodynamic limb vein injection: current applications, hurdles and possible optimizations

Abstract: Hydrodynamic limb vein injection is an in vivo locoregional gene delivery method. It consists of administrating a large volume of solution containing nucleic acid constructs in a limb with both blood inflow and outflow temporarily blocked using a tourniquet. The fast, high pressure delivery allows the musculature of the whole limb to be reached. The skeletal muscle is a tissue of choice for a variety of gene transfer applications, including gene therapy for Duchenne muscular dystrophy or other myopathies, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 133 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, we investigated the limb perfusion injection method, as it is a scalable and regionally restricted delivery approach, yet it can target multiple skeletal muscle groups. Hydrodynamic injection with a large volume is a major approach for delivering DNA vectors 41 ; however, our injection volume (for the 5 mL/kg condition, 125 µL per leg per 25 g of mouse) is much smaller than hydrodynamic limb vein injection methods (i.e., 1 mL per leg 42 ), presumably due to the high delivery activity of LNP. The small volume would be advantageous when performing limb perfusion in patients to avoid any compartment syndrome 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated the limb perfusion injection method, as it is a scalable and regionally restricted delivery approach, yet it can target multiple skeletal muscle groups. Hydrodynamic injection with a large volume is a major approach for delivering DNA vectors 41 ; however, our injection volume (for the 5 mL/kg condition, 125 µL per leg per 25 g of mouse) is much smaller than hydrodynamic limb vein injection methods (i.e., 1 mL per leg 42 ), presumably due to the high delivery activity of LNP. The small volume would be advantageous when performing limb perfusion in patients to avoid any compartment syndrome 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscles are represented by bundles of syncytial cells, named myocytes or muscle fibers. Each of them is surrounded by connective tissue cells, endomysium, while the bundles are in turn coated with perimysium [164]. These connective tissue structures significantly obstruct the entry of therapeutic polyplexes into muscle cells.…”
Section: Muscle Targetingmentioning
confidence: 99%
“…Regional hydrodynamic delivery turns not only the vein but also other vessels into a potential route for effective delivery, although it is necessary to place outflow blockades at the corresponding vasculatures when the injection is performed in an antegrade fashion, such as through arteries or portal veins. In small animals, not only the liver but also the kidneys [12,[43][44][45], muscle [12,[46][47][48][49], pancreas [50], gonads [39], hepatocellular carcinoma [51,52], and brain tumors [53] have been targeted in vivo, while, to date, the liver, kidneys, and muscles are the targeted organs in large animals.…”
Section: Target Animals Organs and Routes Of Injectionmentioning
confidence: 99%
“…RV [12,44,45,60] RV [12] MSL TA, LV, TV [46][47][48]61,62] LV, LA * [12,49,[63][64][65][66][67] LV [26] LV, LA [36,67] LV, LA [39,40] PCAS SMV [50] GND LA, GV, GA [39] HCC HA [51] BT CA [22, To target the muscles, the tail artery [61] or corresponding limb veins or arteries were utilized, including the brachial/popliteal arteries, the great saphenous vein [26,39,40,47,48,62], the dorsalis pedis vein [49,63,64], the cephalic vein [40], the median vein [40], and the femoral vein [65] and artery [66,67]. It was reported that injection of papaverine/histamine into the target vasculature enhances delivery efficiency in muscles by relaxing the endothelial shield [66,67].…”
Section: Target Animals Organs and Routes Of Injectionmentioning
confidence: 99%